Where is the Sunshine Vitamin? A Cross Sectional Study of Vitamin D Status among Rural Adolescent Boys and Girls - Satyanarayana, Pradeep Tarikere; Ravishankar,; T Y, Susanna; Reddy, Sudha; Navya, (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Background: Traditionally labeled as Sunshine Vitamin, Vitamin D is endogenously produced in the skin when exposed to Ultraviolet B rays. Despite this abundantly available Vitamin D, Vitamin D Deficiency is extremely common among the general population. A few reasons identified for this possible silent epidemic in various parts of the world and also a tropical country like India were religious body covering habits, staying indoors for the majority of daytime, and lack of open spaces and direct access to sunlight in high human density habitations resulting in the high prevalence of Vitamin D deficiency among adolescents. Materials and Methods: The present study was a cross-sectional study carried out from January 2021 to July 2022 for a period of 1 year 6 months at various government rural high schools in Kolar, Karnataka, India. All adolescents who were aged 11-18 years belonging to 9th and 10th standard were included in the study after consent and assent. Adolescent boys and girls with any pre-existing mental health illness were excluded from the study. Vitamin D3 levels were assessed by using VITROS Immunodiagnostic products using a 25-OH Total reagent pack. All data was entered in a Microsoft Excel sheet and analyzed using SPSS version 22. To check for association between factors, Chi-square was applied with a level of significance defined as a p-value less than 0.05. Results: Out of 451 students, 272 (60.3%) belonged to the 15-year age group, 235 (52.1%) were studying in 10th standard, 323 (71.6%) belonged to Nuclear Family. 162 (35.9%) had insufficient Vitamin D3 level and 66(14.6%) had deficient levels. Factors like Gender, Class, Type of Family, Timing of outdoor activity and duration of outdoor activity were found to have a statistically significant association with Vitamin D levels among rural adolescents. Conclusion: The present study shows Vitamin D deficiency (VDD) was extremely common among rural adolescents in spite of abundant sunshine even in countries like India suggesting the importance of Nutritional supplementation for school children could be an alterative measure to keep the Vitamin D levels abundant for normal growth and development of children.